This is us - Martínez Santa-María, Luis (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2023)
The characters that we discover in the paintings, despite their apparent accidental and accessory condition in relation to the subject represented, emit powerful signals. They are the ones that make the spectator enter fully into the representation; they are the ones in charge of making the narrative tangible and deep, filling it with movement, and indirectly accentuating the most secret purpose of their message. What is surprising is that their size is small, their presence is secondary and that they seem to have been represented without too much detail, calculation and premeditation. Aware of the loss of quality that current architectural images present we think that studying how carefully the characters were introduced by the master painters is more advisable than ever.
Keywords: Characters; People; Painting; Architectural Drawing; Render